"Are you really proud of me?" Influence of stereotype threats on college athletes' career thoughts. Issue 1 (February 2022) - Hsu, Yawen; Li, Yinru
Removing the vulnerability of a stereotype threat can weaken the stereotype's negative influence. However, stereotype threats can be produced simply by reminding individuals of their stigmatized social identity. In this study, a typical explicit stereotype threat was compared with two types of reports on positive role models to determine whether the influence of stereotypes varied according to the type of report. In total, 178 college athletes were recruited and randomly assigned to the explicit threat group (EX group, n = 46), report on a special case group (RS group, n = 42), report on a general topic group (RG group, n = 46), or neutral report group (control, n = 44). The participants first read a short text with manipulated context. They then completed scales assessing career adaptability and optimism and were asked to choose whether to complete a scholastic test with high or low difficulty or not take the test at all. The career adaptability and optimism scores of the control group were higher than those of the RS and EX group. The career optimism scores of the RG group were higher than those of the EX group. Fewer participants opted for the difficult version of the scholastic text in the EX and RS groups; the majority of participants in these groups chose to not take any test. The results indicated the influence of negative stereotype threats and indicated that reading the news report on the special case did not have a positive and encouraging effect on the participants.